2020
DOI: 10.1002/ppp3.10090
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi affect the concentration and distribution of nutrients in the grain differently in barley compared with wheat

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…AMF inoculation may affect selenium uptake from soil and the level of antioxidant compounds in vegetable crops such as the green asparagus Asparagus officinalis L. Research carried out by [41,42] showed increasing selenium (Se) content in wheat grain through inoculation. It has been found by [43] that AMF modifies the concentration and distribution of nutrients within wheat and barley grain. Inoculation with AMF improves the grain nutritional content in protein, Fe, and Zn [44].…”
Section: Contribution Of Arbuscular Mycorrhizal Fungi To Plant Nutrition and Growthmentioning
confidence: 99%
“…AMF inoculation may affect selenium uptake from soil and the level of antioxidant compounds in vegetable crops such as the green asparagus Asparagus officinalis L. Research carried out by [41,42] showed increasing selenium (Se) content in wheat grain through inoculation. It has been found by [43] that AMF modifies the concentration and distribution of nutrients within wheat and barley grain. Inoculation with AMF improves the grain nutritional content in protein, Fe, and Zn [44].…”
Section: Contribution Of Arbuscular Mycorrhizal Fungi To Plant Nutrition and Growthmentioning
confidence: 99%
“…Wheat ( Triticum aestivum L.) is a major cereal plant grown under diverse climatic conditions (Marris, 2008). The positive contribution of cultured AMF towards wheat growth, quality and yield is well studied (Treseder, 2013; Lehmann and Rillig, 2015; Watts‐Williams and Gilbert, 2019). However, the contribution of naturally occurring AM fungal communities in agroecosystems to growth‐related traits (in terms of nutrient concentrations and grain quality) is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, Salomon et al ( 2022 ) evaluated 25 commercial mycorrhizal inoculants sold in Australia, Europe, and North America in pot trials and concluded that only one product increased mycorrhizal colonisation of highly mycorrhiza-responsive plants ( Lycopersicum esculentum and Allium ameloprasum ) in non-sterile soil, and highlighted the need for more rigorous quality control of these products and more field trials. Pot experiments using arable soils with the addition of a single species commercial AMF inoculum ( Rhizophagus irregularis ) have shown increases in wheat root mycorrhiza colonisation but had little, or even negative effects on macronutrient uptake and concentrations in wheat grains (Elliott et al, 2021 ; Watts-Williams and Gilbert, 2021 ), suggesting that mycorrhiza may often play a limited role in wheat nutrition in long-term arable soils. AMF are, normally, functionally most important for plant P nutrition.…”
Section: Discussionmentioning
confidence: 99%